Aromatherapy Management to Reduce Stress - Puput Mulyono; Singgih Purnomo (Jurnal Visi Manajemen, 2025)
Background: Stress is a major health threat. According to the 2022 adolescent mental health survey, 15.5 million (34.9 percent) adolescents experience mental problems and 2.45 million (5.5 percent) adolescents experience mental disorders. The results of a survey at the University of Indonesia showed that 50% of students who were doing their thesis experienced stress. This can be overcome with non-pharmacological therapy using peppermint incense aromatherapy to reduce stress levels when preparing a thesis for "X" University students. Method: The research design used in this study was quasi-experimental with a pre-test-post-test approach with a control group. The sampling technique used was probability sampling with a simple random sampling method and obtained 58 respondents. Results: Based on analysis using SPSS 24.0, the average value (mean) of the reduction in stress levels in the experimental group was 2.76, while the reduction in stress levels in the control group was 0.00. Apart from that, the results of the paired t test in the experimental group obtained a value of Pv = 0.000 ( alpha = 0.05) which shows the influence of peppermint incense aromatherapy on reducing stress levels when preparing a thesis for students at "X" University, while in the control group the value Pv = 1,000 (alpha=0.05) which indicates there is no effect on the control group. Apart from that, the results of the Man Whitney test obtained a value of Pv = 0.000 (alpha = 0.05) which shows that there are differences between the experimental group and the control group. Conclusion: Based on the research above, it can be concluded that there is an influence of incense aromatherapy.